Reducing maternal mortality : learning from Bolivia, China, Egypt, Honduras, Indonesia, Jamaica, and Zimbabwe - Koblinsky, Marjorie A. (Washington, DC : World Bank, 2003)
This work provides an analysis of factors reducing maternal mortality through three retrospective case studies in China, Honduras and Zimbabwe; and four research studies in Bolivia, Egypt, Indonesia and Jamaica.
Includes bibliographical references.
oif 06/03/15
Loan
Keywords: Maternal health services -- Developing countries; Mothers -- Mortality -- Developing countries; Social welfare